Electrochemical Reactivity of Chemically Roughened Tungsten Electrodes - Park, In-Tae; Kim, Wan; Kim, Eun-Ji; Bae, Sang-Eun; Kim, Jong-Yun; Shin, Heon-Cheol (Asian Journal of Chemistry, 2013)
A variety of rough tungsten electrodes were created and their surface morphology and apparent electrochemical reactivity were analyzed, in order to explore their feasibility as a highly reactive working electrode in electrochemical cells. For this purpose, tungsten electrodes with different surface irregularities were prepared by a chemical etching process and the self-similar fractal dimensions of their surfaces were determined. Then, the integrated charges for hydrogen evolution on their surfaces were estimated in the potentiostatic condition as a measure of their surface reactivity.